Internal environmental audit of the enterprise as a component of environmental management - Odnorih, Zoriana; Malovanyy, Myroslav; Tkachyk, Yuliia; Romaniuk, Liliana; Krusir, Galina (Видавництво Львівської політехніки, 2024)
The research is devoted to measures to increase the level of environmental safety of an industrial enterprise through the implementation of an internal environmental audit. The organization of the environmental management system at the enterprise was studied in terms of resources, operational planning and management, non-compliance, and corrective actions. Documentation regarding the organization of the internal environmental audit conducted at the enterprise, maintenance of environmental documentation, and obtained permits for emissions from stationary sources was considered. Based on the results of the analysis of the information array about the environmental aspects of the enterprise, corrective recommendations for improving the state of the enterprise in the environmental sphere were developed.
Keywords: environmental aspect of production; risk; pollutant emissions; solid waste